The Implementation of Merdeka Curriculum in Teaching and Learning English at SMK Negeri 1 Bulango Selatan - Dondo, Dondi; Talib, Rasuna Rasid; Mestari, Sri Agriyanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to describe the implementation of the Merdeka Curriculum in teaching and learning English at SMK Negeri 1 Bulango Selatan. The study focuses on six key indicators of learning based on the standard process: interactive, inspiring, enjoyable, challenging, motivating students to participate actively, and providing sufficient space for initiative, creativity, and independence. The research employed a descriptive qualitative method. The data were collected through observation and interviews involving an English teacher. The results indicate that the English teacher has successfully implemented most of the principles of the Merdeka Curriculum. The learning process was interactive, inspiring, enjoyable, and challenging, supported by student participation and the teacher’s efforts to create a positive classroom environment. However, the aspect of providing sufficient space for initiative, creativity, and independence was less implemented. The findings suggest that while the teacher applied the core values of the curriculum effectively, there is still a need for improvement in promoting student-centered learning through project-based and creative activities.